MENUJU SEKOLAH DAN MASYARAKAT INKLUSI YANG MENERIMA ANAK DENGAN SEPENUH HATI - Hayatun Thaibah; Agus Pratomo Andi Widodo; Enny Hardi (Jurnal Sinergitas PKM & CSR, 2023)
Community participation to support the implementation of inclusive education for children with special needs by participating in submitting opinions regarding efforts to implement inclusive education carried out directly or through existing institutions, deliberating in making decisions regarding determining school programs, joint decisions including in proposing suggestions, criticism and straightening out inappropriate problems and being responsible for the successful implementation of the joint program. The aim of this service is to increase the awareness of teaching staff and the community about children with special needs in an inclusive world, provide sufficient education and information for teaching staff and the community about children with special needs in understanding an inclusive world and to find out how far the community and teaching staff understand about children with special needs in understanding an inclusive world. General teachers must be fully familiar with inclusive education management, not only special assistant teachers who are graduates of Special Education who provide assistance, but general teachers must learn a lot about children with special needs so that they do not experience difficulties. deal with their students who have obstacles. Through this seminar activity, they finally realized that children with special needs deserve to receive education according to their level and educators are interested in learning about inclusive education in more depth if there is an invitation for Technical Guidance regarding Children with Special Needs.